2004
DOI: 10.1016/j.foodres.2003.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Sensory characteristics of cold-smoked Atlantic salmon (Salmo salar) from European market and relationships with chemical, physical and microbiological measurements

Abstract: Samples of different brand names of cold-smoked salmon products were purchased in supermarkets in six different European countries (Belgium, Denmark, France, Germany, Italy and United Kingdom), to classify and select products of smoked salmon for preference establishment. From the 117 products obtained, 60 were selected to characterise the qualities of products available to European consumers. These 60 products of smoked salmon were then ordered directly from the producers in each country. Altogether 57 produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
102
2
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(117 citation statements)
references
References 31 publications
8
102
2
5
Order By: Relevance
“…This was also observed for the smoked trouts, which presented an estimated 20% increase of protein when compared to fresh trout. Cardinal et al (2004) evaluated and correlated the sensory characteristics of smoked salmon obtained in European markets to physical-chemical and microbiological parameters and achieved values of moisture (62.9g/100g) and lipids (10.4g/100g) which were very close to the ones found in this work. The quality parameters thought to be applicable to fish quality evaluation usually include flavor, texture, and global appearance (Borresen, 1992).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…This was also observed for the smoked trouts, which presented an estimated 20% increase of protein when compared to fresh trout. Cardinal et al (2004) evaluated and correlated the sensory characteristics of smoked salmon obtained in European markets to physical-chemical and microbiological parameters and achieved values of moisture (62.9g/100g) and lipids (10.4g/100g) which were very close to the ones found in this work. The quality parameters thought to be applicable to fish quality evaluation usually include flavor, texture, and global appearance (Borresen, 1992).…”
Section: Resultssupporting
confidence: 74%
“…Previous studies with smoked salmon showed that the coloration was directly related to pigments received in their diet (Sheehan et al, 1998), with the lipid content in the fish (Rora et al, 1998) and the parameters applied during smoking ). Evaluation and correlating the sensory characteristics of smoked salmon purchased in European markets with the physical-chemical and microbiological parameters, Cardinal et al (2004), found values between 45.4 to 61.8, 13.4 to 34.2, and 16.9 to 33.7, respectively for parameters L * , a * and b * . These results were similar to the ones found in this work.…”
Section: Resultsmentioning
confidence: 99%
“…La variable L* representa la luminosidad (L* = 0 para negro y L* = 100 para blanco), mientras la escala a* representa la dimensión rojo/verde (a* > 0 para rojo y a* < 0 para verde). La escala b* representa la dimensión amarillo/azul (b* > 0 para amarillo y b* < 0 para azul (Cardinal et al, 2004). Se estimaron las diferencias de color (∆E) de acuerdo a la Ec.…”
Section: Análisis De Texturaunclassified
“…The microbial ecology of coldsmoked fishery products has been intensively studied (Bernardi, Ripamonti, Campagnoli, Stella & Cattaneo, 2009;Gonzàles-Rodrìguez, Sanz, Santos, Otero & Garcia-Lopez, 2002;Joffraud, Leroi, Roy &Berdaguè, 2006;Lannelongue, hanna, Finne, Nickelson & Vanderzant,1982;Leroi, Jooffraud, Chevalier &Cardinal, 1998;Leroi, Joffraud, Chevalier & Cardinal, 2001;Leroi, 2010;Lyhs, Björkroth, Hyytiä, & Korkeala,1998;Truelstrup Hansen and Huss, 1998). The initial bacterial load closely depends on the hygienic conditions of processing and production Truelstrup Hansen and Huss, 1998), and it is represented by lactic acid bacteria (LAB), Enterobacteriaceae, Shewanella putrefaciens, Aeromonas spp., Pseudomonas spp., Photobacterium phosphoreum, and Brochothrix thermosphacta (Cardinal, Gunnlaugsdottir, Bjoernevik, Ouisse, Vallet, & Leroi, 2004;Jorgensen and Huss, 1989;Leroi et al, 2001;2010;Lyhs et al, 2007;Jaffrès, Sohier, Leroi, Pilet, Prévost, Joffraud &Dousset, 2008;Laursen, Bay, Cleenwerck, Vancanneyt, Swings, Dalgard &Leisner, 2005;Truelstrup Hansen, Gill, Drewer Røntved &Huss, 1996;Civera, Parisi, Amerio, & Giaccone, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The dominant microflora in both vacuumpacked and MAP-packed smoked fish at the end of the retention period was often found to be LAB: the predominance of this group is not totally clear, but it seems that they are well suited to the particular pH, water phase salt (WPS) and salt concentration of smoked products (Bernardi et al, 2009;Cardinal et al, 2004;Laursen et al, 2005;Leroi et al, 2000;Lyhs, Lahtinen & Schelvis Smith, 2007;Samelis, Maurogenakis & Metaxopoulos, 1994). Also Pseudomonas spp., which initially contaminate the raw fish meat, could cause the spoilage in VP due to residual oxygen or oxygen permeability of the protective film.…”
Section: Introductionmentioning
confidence: 99%